Return to the past or bet on the future? - Quiroz-Velasco, María-Teresa (1986)
The electoral triumph of the APRA party in the recent presidential elections in Peru has provoked multiple interpretations. After 55 years of struggle for power (of which remained under the exclusive and patriarchal leadership of the head and founder of APRA, Victor Raul Haya de la Torre), the APRA party came to power in 1985, this time under the direction of a new leader, Alan García Pérez.